Developing Digital Comics as Character Learning Media for Elementary School Students - Rohmanurmeta, Fauzatul Ma’rufah; Dewi, Candra (Universitas Negeri Malang, 2020)
Students are expected to learn and conserve the natural environment. Therefore, it is necessary to integrate technology with character values in the form of developing digital comics for environmental preservation based on character values. This study was designed to develop digital comic learning media for environmental preservation based on character values by using of ADDIE development model. were collected using both qualitative and quantitative approaches. Qualitative data were in the form of suggestions, criticisms, responses, and input as described in the questionnaire from the expert judgment. Meanwhile, quantitative data included in the form of percentage values from expert judgment questionnaires arranged on a multilevel scale. Observation, interviews, questionnaires, and tests were used to gather the data. The findings of this study suggested that materials appropriateness and student learning achievement exceed the minimum criteria value set previously. These results show that digital comic learning media based on the character values in integrative thematic learning are declared very feasible and ready to be implemented in integrative thematic learning.